Perkembangan Kesadaran Beragama Pada Usia Dewasa (Tinjauan Psikologis Dan Agama Islam) - Nani M. Sugandhi (STAI Siliwangi Bandung, 2016)
Referred to as a potential creature, as a human being saved some innate ability that can be developed. One development aspect that is very relevant and influence on other aspects of development, is the development aspect of the religious consciousness. Religious awareness refers to the individual spiritual aspects that associated with belief in Allah and actualization through worship to the God, both hablumminallah and hablumminannas. Faith in Allah SWT and its actualization in worship is the result of the internalization, that are the process of recognition, understanding, and awareness of one's self to religious values. In a review of psychological, tasks of individuals development who have entered the phase of adulthood, should have been able to actualize, express (realize) the values ​​of religion in his whole life as a whole (kaffah), both in attitude, words and deeds (in the life of personal and social). Similarly, in the view of Islam, religious maturity in adulthood, should be able to lead towards the development of religious awareness level to enforce amar ma’ruf and nahyi munkar, or preaching tinged with ruhul jihad fisabilillah (fighting spirit in the way of Allah) to spread kindness values or benefit for the welfare of human life (rahmatan lil 'alamin), and prevent or eradicate evils, idolatrous, tyranny, vices, and hypocrisy. Aamiiin ya Robbal 'Alamiiin